THE PRINCIPAL'S STRATEGY IN DEVELOPING EXTRACURRICULAR ACTIVITIES AT MTS TERPADU BERKAH PALANGKA RAYA - Bambang; Musyarafah; Rio Irawan (CV. Radja Publika, 2026)
The strategy of the madrasah principal at MTs Terpadu Berkah Palangka Raya in developing extracurricular activities with the main aim of fostering holistic student development, through extracurricular activities, it is necessary to make commitment efforts that consider the positive and negative impacts. This study aims to describe how the strategy for developing extracurricular activities at MTs Terpadu Berkah Palangka Raya. This study uses a descriptive qualitative method using data sources taken from three informants through in-depth interviews selected using purposive sampling techniques , the informants selected are the Madrasah Principal, Extracurricular Teacher, and Students participating in extracurricular activities at MTs Terpadu Berkah. All interview results were then analyzed using data reduction techniques, data presentation, and conclusion drawing. The results of the analysis in this study are: 1) Extracurricular activities at MTs Terpadu Berkah consist of 2 types of groups, namely 5 mandatory extracurriculars and 4 electives with a vision, mission and objectives that are closely related to the Qur'an. 2) The strategy for developing extracurricular activities at MTs Terpadu Berkah Palangka Raya consists of 3 steps, namely Strategy Formulation by forming a vision, mission and objectives. The principal uses SWOT analysis steps to find opportunities, threats, strengths and weaknesses. Followed by Strategy Implementation, namely forming an extracurricular organizational structure. Ending with Strategy Control in developing extracurricular activities at school, namely by setting standards, providing performance recognition, making work comparisons with work standards, and taking corrective actions that can be seen from weekly and monthly accountability reports, as well as attendance lists for each activity, both weekly and monthly.